2006
DOI: 10.1007/bf02935340
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative response mechanisms in halophytes: Their role in stress defence

Abstract: Normal growth and development of plants is greatly dependent on the capacity to overcome environmental stresses. Environmental stress conditions like high salinity, drought, high incident light and low or high temperature cause major crop losses worldwide. A common denominator in all these adverse conditions is the production of reactive oxygen species (ROS) within different cellular compartments of the plant cell. Plants have developed robust mechanisms including enzymatic or nonenzymatic scavenging pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
161
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(179 citation statements)
references
References 131 publications
4
161
0
5
Order By: Relevance
“…In plants, scavenging of superoxides occurs by differential regulation of SOD isoforms (Wang et al, 2004). Studies on regulation of individual isoforms of SOD are therefore important because their role during salt stress could be elucidated (Jithesh et al, 2006). However, all the previous reports reflect the effect of NaCl stress on total SOD activity.…”
Section: Gr) Total Cat (A) Pod (B) Apx (C) Gr (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, scavenging of superoxides occurs by differential regulation of SOD isoforms (Wang et al, 2004). Studies on regulation of individual isoforms of SOD are therefore important because their role during salt stress could be elucidated (Jithesh et al, 2006). However, all the previous reports reflect the effect of NaCl stress on total SOD activity.…”
Section: Gr) Total Cat (A) Pod (B) Apx (C) Gr (D)mentioning
confidence: 99%
“…Recently, many authors addressed investigations on naturally salt tolerant plants (or halophytes) in which the mechanisms of salt tolerance are fully developed and functional to make them productive under stress. Jithesh et al (2006) reviewed the regulation of antioxidant enzymes under salt stress in halophytes, especially those of mangroves. They concluded that antioxidant enzymes protect halophytes from deleterious ROS production during salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Stress response mechanisms in halophytes have been reviewed by Jithesh et al (2006). They note that salt stress, which affects cellular membranes, enzyme activities and the photosyntethic system, is largely caused by the damage from the production of reactive oxygen species (ROS) (Jithesh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They note that salt stress, which affects cellular membranes, enzyme activities and the photosyntethic system, is largely caused by the damage from the production of reactive oxygen species (ROS) (Jithesh et al, 2006). Plants have evolved two antioxidative pathways to combat damage from ROS: an enzymatic pathway, which involves enzymes such as super oxide dismutase, and catalase, and a nonenzymatic pathway which includes antioxidants such as tocopherol, carotenoids, ascorbate, phenolic compounds, alkaloids, glutathione and non-protein amino acids that scavenge free radicals (Gill and Tuteja, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation